Genomic and functional characterization of a novel halophilic bacteriophage targeting carbapenem-resistant Klebsiella pneumoniae - Sahar Abed; Masoumeh Beig; Sepideh Soltani; Mohadeseh Pahlevani; Peter Speck; Morvarid Shafiei; Abdolrazagh Hashemi Shahraki; Abozar Ghorbani (PLoS ONE, 2026)
Carbapenem-resistant Klebsiella pneumoniae (CRKP) is a multidrug-resistant (MDR) pathogen causing severe infections in immunocompromised patients, prompting the exploration of alternative therapies like bacteriophage therapy. In this study, we isolated and characterized a novel halophilic lytic bacteriophage, Halo KS-7, targeting K. pneumoniae , and used an AI-driven annotation pipeline in Python to analyze its genome and therapeutic potential. Bacteriophages were isolated from Hospital wastewater, purified through plaque isolation, and confirmed using the double-layer agar method. Morphological analysis via transmission electron microscopy (TEM) and plaque assays assessed lytic activity. In vitro assays, including one‑step growth curve and MOI determination, were performed to evaluate the replication kinetics and lytic activity of bacteriophage Halo KS‑7 against carbapenem‑resistant Klebsiella pneumoniae. In vivo efficacy was assessed using a BALB/c mouse wound infection model by monitoring wound contraction and performing blinded histopathological analysis following phage treatment. DNA sequencing was done using Illumina HiSeq 2000, followed by genome assembly, AI-guided annotation, gene prediction, protein function classification, and comparative genomics using CLC Genomics Workbench. We also evaluated host range, temperature stability, pH sensitivity, and salt stress tolerance to assess therapeutic potential. Halo KS-7 exhibited strong lytic activity against CRKP and was classified as a Myoviridae bacteriophage by TEM. Phenotypic assays demonstrated optimal activity at 37 °C and neutral pH, effective activity from pH 4–10, and enhanced performance in high-salinity conditions. Bacteriophage Halo KS-7 exhibited a short latent period (~20 min), a modest burst size (5.73 PFU/cell), and optimal antibacterial activity at MOI 0.1, resulting in sustained suppression of K. pneumoniae growth in vitro . In vivo , Halo KS-7 treatment significantly enhanced wound healing in infected BALB/c mice, achieving near-complete wound closure, effective infection control, and improved histopathological regeneration comparable to uninfected controls. Halo KS-7 have 58.716 kb linear dsDNA genome (44.4% G + C), contains 49 predicted ORFs, lacks integrase, lysogeny, or antibiotic-resistance genes, and includes three tRNA genes (tRNATyr, tRNAPro, and tRNAAsn). It also includes a toxin gene and auxiliary factors like MazG, pyrophosphatase, and HNH endonucleases that enhance bacterial killing without promoting horizontal gene transfer or resistance. Functional annotation assigned ~65% of ORFs to structural, replication, and packaging roles. Comparative genomics showed moderate similarity to other Myoviridae but with distinct accessory features, emphasizing its novelty and therapeutic value. Halo KS-7 is a novel, strictly lytic bacteriophage with strong antibacterial activity and stress resilience, supporting its use as a promising biocontrol agent against CRKP and its potential for clinical development in managing MDR infections.